Psychology and religion : an introduction - Argyle, Michael (London ; New York : Routledge, 2000)
Michael Argyle's book is a clear and accessible introduction to the psychology of religion. One of the world's most famous psychologists, Argyle ranges over the whole of psychology to look at the results of psychology's study of religion including those of his own important experiments. Psychology and Religion is full of fascinating and surprising insights into people and their religious worlds.
1. The relation between psychology and religion -- 2. Socialisation -- 3. The effect of personality -- 4. The extent and varieties of religious experience -- 5. The causes and effects of religious experience -- 6. Religious beliefs -- 7. Freud's and Jung's accounts of religious belief -- 8. Worship and prayer -- 9. Ritual and charisma -- 10. Happiness and the other benefits and costs of religion -- 11. Physical and mental health -- 12. Religious and other origins of morals -- 13. The effect of religion on behaviour -- 14. Secularisation and the present state of religion -- 15. The growth of new religious movements -- 16. Conclusions for religion.
Includes bibliographical references (p. [251]-279) and indexes.
Keywords: Psychology and religion; Psychology, Religious